Peran Jaksa dalam Kasus Anak Pelaku Asusila dan Proses Rehabilitasi Berdasarkan Putusan Nomor XXX/Pid. Sus-Anak/2024/PN Mgg - Okti Indah Lestari; Dinda Rachma Aditya; Faiza Nisrina; Sahilda Lailatul Rahma; Siti Muaviroh; Devi Lusyany; Muhammad Yusuf Rangkuti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the legal process against children who commit indecent crimes and the role of rehabilitation as a recovery effort based on Decision Number XXX/Pid.Sus-Anak/2024/PN Mgg. This investigation uses normative and empirical legal methods by analyzing laws and regulations and judicial practices against children. This investigation purposes to examine the role of the prosecutor in determining the boarding school as a place of rehabilitation and assess the suitability of the prosecutor's charges with the provisions of juvenile criminal law in Indonesia. The findings showed that prosecutors play an important role in determining the form of rehabilitation by coordinating with community supervisors, considering the best interests of the child as stipulated in Law Number 11 of 2012 concerning the Child Criminal Justice System (UU SPPA). The selection of pesantren as a place for rehabilitation reflects an educational approach that not only punishes, but also shapes the morals and character of children so that they can return to society in a better condition. This rehabilitation also provides access to education and guidance in an environment that supports the mental and social recovery of children and prevents repetition of criminal acts.